Audio Visual and Its Impact on Pain During Immunization - Aura Latifah Rahman; Nursasmita, Rizqi; Andi Mayasari Usman (International Health Sciences Journal, 2024)
Background: Immunization is an effort to increase the body's immunity to a disease and makes a significant contribution to reducing child mortality, when children are immunized, it will cause pain and the provision of audio visuals given to children is expected to reduce or divert pain during immunization. Purpose: To determine the effect of audio visual on pain during immunization in toddler children (12-36 months) in the intervention group and control group. Method: This research method is experimental which is a study by looking for the effect of audio visual on immunization pain between the intervention group and the group using a two-group posttest design involving 64 respondents who meet the inclusion criteria. Sampling using random sampling with research instruments using SOPs and FLACC. Results: The results obtained were that in the intervention group there were 56.3% of respondents who experienced mild pain and the control group there were 75.1% of respondents who experienced severe pain. Subsequent analysis using the Mann Whitney test obtained a p value of 0.001. Conclusion: Providing audio visuals is proven to have an effect on the pain scale during immunization in toddler.